Forgógépek üzem közbeni mozgásának próbapadi és ipari vizsgálata - Szabó, József Zoltán (Jelenkori Társadalmi és Gazdasági Folyamatok, 2012)
The significance of predictive maintenance and vibration diagnostic increasing continuously in every area of industry. Vibration diagnostics delivers considerable economic benefits for machinery operation. Vibration measurement can show up mechanical problems and harmful effects which acts on the parts throughout the operating period of the machine. This paper describes an alternative method of vibration diagnostic with , Vibshape"moving-animation software. With this program and an vibration analyser the moving of the machines, and the mechanical, structures can be visible. This article shows the basic knowledge of vibration diagnostic with animation program, and a case study from my practice. The case study shows the moving of the machines in main mechanical problems, for example resonance and electrical problem. Across of the case study we can see the resonance problem of a supporting structure and a big blower rotor bar crack.